2000
DOI: 10.1111/j.1432-2277.2000.tb01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C - an accurate marker of glomerular filtration rate after renal transplantation?

Abstract: The performance of serum cystatin C as a screening marker of reduced creatinine clearance in renal transplantation was evaluated and compared to serum creatinine. In addition we studied whether cystatin C accurately reflects creatinine clearance over the entire range of transplant function. Serum cystatin C, serum creatinine, and creatinine clearance were measured in 110 adult renal transplant recipients. Cystatin C detected reduced creatinine clearance with the high sensitivity of 95 YO. Serum cystatin C and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 22 publications
2
14
0
Order By: Relevance
“…Paskalev et al [19]studied 40 transplant recipients and found serum cystatin C to be superior to serum creatinine, determined with the Jaffé method, in diagnostic accuracy but similar to creatinine clearance. In another report, by Herget-Rosenthal et al [16], a large number of patients (n = 110) were enrolled. However, they used creatinine clearance as a measure of GFR, which is associated with several limitations not seen with iohexol clearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paskalev et al [19]studied 40 transplant recipients and found serum cystatin C to be superior to serum creatinine, determined with the Jaffé method, in diagnostic accuracy but similar to creatinine clearance. In another report, by Herget-Rosenthal et al [16], a large number of patients (n = 110) were enrolled. However, they used creatinine clearance as a measure of GFR, which is associated with several limitations not seen with iohexol clearance.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports on measurement of serum cystatin C in patients with renal transplants [16, 17, 18, 19]. In three of the studies, serum cystatin C was suggested to be superior to serum creatinine [17, 18, 19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a steady-state muscular mass balance, the plasma creatinine concentration is assumed to reflect glomerular filtration rate (GFR) (15). However, plasma creatinine is far from being an ideal marker of GFR, despite its convenience and low cost (16).…”
Section: Discussionmentioning
confidence: 99%
“…To date, data on the diagnostic accuracy of cystatin C in renal transplant patients from small study groups have been published. Only one larger study comprising 110 patients did not show any diagnostic advantage of cystatin C [16][17][18][19][20][21][22][23][24][25]. We, therefore, assessed the diagnostic accuracy of serum creatinine and cystatin C as markers of GFR in 173 consecutive adult renal transplant patients.…”
Section: Introductionmentioning
confidence: 99%